STRATEGI PEMBANGUNAN PERKEBUNAN KELAPA DI KABUPATEN ROKAN HILIR - Gulat Medalie Mas Manurung (Jurnal Sagu, 2004)
In view of national development direction and natural resource potency of Regency Rokan Hilir, henceagricultural sector become economic backbone. Government of Regency Rokan Hilir it is fact that its societyhave to perform persistent effort develop; economic system including development of coconut plantation basedon agroindrustry and agrobisnis. Some supporting reason to make coconut as a prime commodity of RokanHilir Regency are: F"irstly, from agronomy point of view, this region has land capacity to support the commoditydevelopment; Secondly, human resource in Rokan Hilir sector, have king exorience in coconut commodity.sothat they have owned agronomic ability to work in this; thirdly, potential land for the development of cropplantation like coconut is still available; Fourthly, otlier crop plantation like cacao and coffee very to bepotential developed asintercropping plants among coconut plant, which can avoid farmer from loss due touncertainly coconut price so that income of farmers can be improved; Fiftlily, Indonesia position in the worldcoconut trade become more strong, marked by Indonesia position as biggest .second coconut exporter after thePhilippina. SWOT analysis show that opportunity and strength factor are very potential in the development ofcoconut agroindustry and agribusiness in Rokan Hilir Regency. Ba.sed the identified potency, opportunity,main problem and constraint the strategy for the coconut development shouth be directed to two especialaspect namely agroindustry and agrobusiness using efTicient technology and also industrial home andniiirkct oriented.